Violence symbolique et résistances populaires - Ugo Palheta
This article reassesses the concept of « symbolic violence » which was introduced by Pierre Bourdieu in his works about school systems, and more generally as the French scholar tried to address the enigmatic character of the perpetuation of domination relations. After asserting the position of this concept within the (social) reproduction paradigm, this paper emphasizes the theoretical debates opened by the uses of this concept in the social sciences (and particularly in education sciences), especially initiated by the works of Paul Willis, but also Claude Grignon and Jean-Claude Passeron. Then, based on a study I conducted about young people in vocational schools, I examine the conditions that allow a positive and rigorous use of this concept in education sciences and I highlight the inevitable dead angles and tension points of this concept, which lead to rethink the relation of young people who choose these tracks (or are directed towards these tracks) with school domination.